Best Answer

y = f(x) = (2x + 1)/(x - 1)y*(x - 1) = (2x + 1)

xy - y = 2x + 1

xy - 2x = y + 1

x(y - 2) = y + 1

so x = (y + 1)/(y - 2) assuming yâ‰?

2.

So the inverse function is f-1(x) = (x + 1)/(x - 2)

Q: How do you find the inverse of the function f of x equals 2x plus 1 divide x-1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.

change it to an improper fraction and then divide it

To find the inverse, replace y with x, and x with y. So, the inverse of the equation is: x = 4yWhich is equal to:y = x/4

If f(x) = 4x + 12, to find the inverse, reverse the actions of the elements of the function in "reverse" order. The last thing done is "+ 12", so reverse that first by "- 12" The previous thing done was "× 4n, so reverse that by "÷ 4", but note that the divide takes precedence over subtract, so the previous step needs to be in brackets. Thus if the inverse of f(x) is g(x), g(x) = (x - 12) ÷ 4

The inverse of the logarithm of a number is ten to the number, meaning that the number is the exponent. In this case, 10^-3.1 equals approximately .0007943.

Related questions

To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.

change it to an improper fraction and then divide it

The inverse of a logarithmic function is an exponential function. So to find the "inverse" of the log function, you use the universal power key, unless you're finding the inverse of a natural log, then you use the e^x key.

To find the inverse simply switch the x's with the y's so... inverse of y=x is x=y

Divide 1 by the number. The multiplicative inverse of 7 is 1/7, for example.

Check out the acos function.

To find the inverse, replace y with x, and x with y. So, the inverse of the equation is: x = 4yWhich is equal to:y = x/4

To find the inverse of a function, simply switch the variables x and y. So for the function y=7x+3, the inverse would be x=7y+3, or y=(x-3)/7.

The only trig functions i can think of with horizontal assymptotes are the inverse trig functions. and they go assymptotic for everytime the non-inverse function is equal to zero.

The inverse of a function can be found by switching the independent variable (typically the "x") and the dependent variable (typically the "y") and solving for the "new y". You can also create a t-chart for the original function, switch the x and the y, and graph the new relation.You will note that a function and its inverse are symmetrical around the line "y = x".Sometimes the inverse of a function is not actually a function; since it doesn't pass the "vertical line test"; in this case, you have to restrict the new function by "erasing" some of it to make it a function.

If f(x) = 4x + 12, to find the inverse, reverse the actions of the elements of the function in "reverse" order. The last thing done is "+ 12", so reverse that first by "- 12" The previous thing done was "× 4n, so reverse that by "÷ 4", but note that the divide takes precedence over subtract, so the previous step needs to be in brackets. Thus if the inverse of f(x) is g(x), g(x) = (x - 12) ÷ 4

If its a fraction then we can change the numerators and denominators upside down .This is in case of fraction.